Appendiceal Mucocele Presenting as a Right Adnexal Mass: A Case Report - Grigor Gortchev; Slavcho Tomov; Dobromir Dimitrov; Vasil Nanev; Tatyana Betova (Obstetrics and Gynecology International)
A 68-year-old female presented to the Gynecologic Oncology Clinic with a right-lower quadrant abdominal mass 3×4 cm in diameter palpable on pelvic examination. Her routine laboratory tests were normal. Transvaginal ultrasonography revealed a cystic mass in the right adnexa 3.9 cm in diameter, which was thought to arise in the ovary. At the time of laparoscopy, a 3×4 cm tumor arising from the distal end of the appendix was noted. A laparoscopic appendectomy with tumor removal was performed. Histologic examination of the surgical specimen revealed a mucocele of the appendix (AM). Although rare, this tumor should be considered in the differential diagnosis of a right adnexal mass. These tumors can be identified laparoscopically and removed by minimally invasive surgery.